2014
DOI: 10.1128/mcb.00850-13
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Tyrosine Kinase Ubiquitylation Involves the Dynamic Regulation of Cbl-Spry2 by Intersectin 1 and the Shp2 Tyrosine Phosphatase

Abstract: Ubiquitylation of receptor tyrosine kinases (RTKs) regulates their trafficking and lysosomal degradation. The multidomain scaffolding protein intersectin 1 (ITSN1) is an important regulator of this process. ITSN1 stimulates ubiquitylation of the epidermal growth factor receptor (EGFR) through enhancing the activity of the Cbl E3 ubiquitin ligase. However, the precise mechanism through which ITSN1 enhances Cbl activity is unclear. Here, we demonstrate that ITSN1 interacts with and recruits the Shp2 tyrosine pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
1
16
1
Order By: Relevance
“…By combining miRNA and mRNA microarray results, of all the seven predicted target genes of miR‐122‐5p, we selected Sprouty2 for further study. Sprouty2 (Spry2) belongs to a member of highly conserved Sprouty signal transduction proteins family, whose unique carboxyl‐terminal cysteine‐rich domain is essential for the inhibition of receptor tyrosine kinase signalling . As an inhibitor of the Erk/MAPK signalling pathway, it is required for growth factors stimulated translocation to membrane ruffles and interacts with various early MAPK pathway‐associated proteins that play an important role in cell proliferation, differentiation and migration .…”
Section: Discussionmentioning
confidence: 99%
“…By combining miRNA and mRNA microarray results, of all the seven predicted target genes of miR‐122‐5p, we selected Sprouty2 for further study. Sprouty2 (Spry2) belongs to a member of highly conserved Sprouty signal transduction proteins family, whose unique carboxyl‐terminal cysteine‐rich domain is essential for the inhibition of receptor tyrosine kinase signalling . As an inhibitor of the Erk/MAPK signalling pathway, it is required for growth factors stimulated translocation to membrane ruffles and interacts with various early MAPK pathway‐associated proteins that play an important role in cell proliferation, differentiation and migration .…”
Section: Discussionmentioning
confidence: 99%
“…5F), whereas earlier reports have shown that Spry2 dominant-negative mutant unable to bind c-Cbl did not function as dominant-negative form and kept EGFR levels unchanged Haglund et al, 2005]. Although the precise mechanism through which Y55A-Spry2 suppresses endogenous Spry2 and c-Cbl interaction remains unclear, it was recently reported that intersectin1 (ITSN1), which stimulates ubiquination of EGFR through enhancing the activity of Cbl, interacts with and recruits the Shp2 tyrosine phosphatase to Spry2 to enhance its dephosphorylation, thereby disrupting the inhibitory effect of Spry2 on Cbl and increasing EGFR ubiquitination [Okur et al, 2014]. While our results indicate that Y55A-Spry2 enhances EGFR ubiquitination and degradation, our data do not address the functional consequences of this Spry2-Cbl complex and Y55A-Spry2 interaction.…”
Section: Discussionmentioning
confidence: 99%
“…dynamin and synaptojanin) [1, 9, 10], actin rearrangement (e.g. N-WASP) [11], cell survival (e.g., PI3KC2β) [12], and cell signaling (e.g., Sos, Cbl, and RALT) [1316] (reviewed in [2, 7, 17]). Some ITSN orthologs in lower eukaryotes have fewer SH3 domains.…”
Section: Structure and Subcellular Localizationmentioning
confidence: 99%
“…ITSN activates Cbl through a complex network of protein:protein interactions. In addition to binding Cbl, ITSN binds Spry2, a Cbl inhibitor, and the tyrosine phosphatase Shp2, a Cbl activator [16, 60]. These interactions lead to decreased tyrosine phosphorylation of Spry2, which disrupts binding to Cbl’s N-terminal SH2-like domain, thereby resulting in Cbl activation.…”
Section: Functionmentioning
confidence: 99%
See 1 more Smart Citation